Peanut Endophytic Phosphate Solubilizing Bacteria Increase Growth and P Content of Soybean and Maize Plants - Lucero, Cinthia Tamara (2021)
Phosphorus (P) is a limiting factor of plant development due to its low availability in the soil. The use of endophytic phosphate solubilizing bacteria as a more sustainable alternative to the use of chemical phosphorus fertilizers is proposed in this study. The objectives were to analyze the effect of simple inoculations of native peanut endophytic phosphate solubilizing bacteria on plant growth promotion and P content of soybean and maize and to evaluate their survival and endophytic colonization capacity on these plants. In addition, bacterial plant cell wall degrading enzymes activities in presence or absence of root exudates was determined. Soybean, maize and peanut plants were grown on a microcosm scale and inoculated with Enterobacter sp. J49 or Serratia sp. S119. It was observed that phosphate solubilizing strains promoted the growth of maize and soybean plants and contributed significantly P to their tissues. A significant increase in the phosphate solubilizing capacity of the plant rhizosphere after the end of the assay was observed. The strains showed to survive in plant’s growth substrate and in the case of Enterobacter sp. J49, it showed also to colonize endophytically maize and soybean. Root exudates of the three plants showed to produce changes in pectinase and cellulase activities of the strains. The bacterial strains analyzed in this study constitutes potential sources for the formulation of biofertilizers for their application for several crops in agricultural soils with low P content.